Partial spreads in PG(4,2) and flats in PG(9,2) external to the Grassmannian G1,4,2 - Shaw, Ron; Gordon, Neil A.; Maks, Johannes G. (DISCRETE MATHEMATICS, 2005)
We consider the following 'even hyperplane construction'of flats in the projective space PG(9, 2) = P(boolean AND(2) V(5, 2)) which are external to the Grassmannian G(1,4,2) of lines of PG(4,2). Let the Grassmann image in G(1,4,2) of a partial spread S-r = {mu(1),..., mu(r)} in PG(4,2) be C-r = {m(1,)..., m(r)}. Then C-r is an r-cap on G(1.4.2). Using the recent classification [N.A. Gordon, R. Shaw, L.H. Soicher, Classification of Partial Spreads in PG(4,2), pp. 63, available from: http://www.hull.ac.uk/maths/people/rs/staffdetails. html] of partial spreads in PG(4,2), we determine those partial spreads S-r such that the projective space E(C-r) = < C-r>,en generated by the ((r)(2)) points m(ij) := m(i) + m(j) is an external flat. We show 2 that, in this simple manner, we may construct seven out of the ten GL(5,2)-orbits of external flats. (c) 2005 Elsevier B.V. All rights reserved.
Output ID 23814.
Keywords: Theoretical Computer Science; Discrete Mathematics and Combinatorics